Effector mining from the Erysiphe pisi haustorial transcriptome identifies novel candidates involved in pea powdery mildew pathogenesis. (11th October 2019) - Sharma, Gunjan; Aminedi, Raghavendra; Saxena, Divya; Gupta, Arunima; Banerjee, Priyajit; Jain, Deepti; Chandran, Divya
Summary: Pea powdery mildew (PM) is an important fungal disease caused by an obligate biotroph, Erysiphe pisi ( Ep ), which significantly impacts pea production worldwide. The phytopathogen secretes a plethora of effectors, primarily through specialized infection structures termed haustoria, to establish a dynamic relationship with its host. To identify Ep effector candidates, a cDNA library of enriched haustoria from Ep ‐infected pea leaves was sequenced. The Ep transcriptome encodes 622 Ep candidate secreted proteins (CSPs), of which 167 were predicted to be candidate secreted effector proteins (CSEPs). Phylogenetic analysis indicates that Ep CSEPs are highly diverse, but, unlike cereal PM CSEPs, exhibit extensive sequence similarity with effectors from other PMs. Quantitative real‐time PCR of a subset of EpCSEP / CSPs revealed that the majority are preferentially expressed in haustoria and exhibit infection stage–specific expression patterns. The functional roles of EpCSEP001, EpCSEP009 and EpCSP083 were probed by host‐induced gene silencing (HIGS) via a double‐stranded (ds) RNA‐mediated RNAi approach. Foliar application of individual EpCSEP / CSP dsRNAs resulted in a marked reduction in PM disease symptoms. These findings were consistent with microscopic and molecular studies, suggesting that these Ep CSEP/CSPs play important roles in pea PM pathogenesis. Homology modelling revealed that Ep CSEP001 and Ep CSEP009 are analogous to fungal ribonucleases and belong to the RALPH family of effectors. This is the first study to identify and functionally validate candidate effectors from the agriculturally relevant pea PM, and highlights the utility of transcriptomics and HIGS to elucidate the key proteins associated with Ep pathogenesis.